A comparative study of impact effect of composite cylinders and type IV pressure vessels. Issue 2 (16th April 2021) - Farhood, Naseer H; Karuppanan, Saravanan; Ya, Hamdan H; Abdul-Lateef, Wisam Essmat
Abstract : Generally, composites are sensitive to transverse impact loading because there is no through-thickness reinforcement for these materials. Specifically, type IV composite pressure vessels and cylinders are more susceptible under impact loading because of the presence of a plastic liner. The main challenges related to the existing composite pressure vessel materials are low toughness, low damage tolerance and high cost. Fiber hybridization is one of the active strategies employed to toughen composites and improve impact damage resistance. Therefore, in this work, the low-velocity impact resistance and induced damage severity of carbon–basalt/epoxy hybrid composites were experimentally studied on different cylinders, under 100 J impact energy. The potential of these new hybrid composites was analyzed for type IV pressure vessels. Composite cylinders with eight cylindrical laminates of different stacking sequences and fiber content ratios were fabricated through the filament-winding technique. Damage characterization was carried out using the scanning electron microscopy technique for both composite cylinders and pressure vessels. The results indicated that basalt/epoxy samples exhibited better impact resistance, energy absorption and lower damage severity than carbon/epoxy samples for both composite cylinders and type IV pressure vessels. Moreover, hybrid composite pressure vessels exhibited better impact performance compared with the pure carbon/epoxy vessel.